Effects of Prolonged Intermittent Fasting Model on Energy Metabolism and Mitochondrial Functions in Neurons. Issue 1 (January 2022) - Pak, Meltem; Bozkurt, Süleyman; Pınarbaşı, Arzu; Öz Arslan, Devrim; Aksungar, Fehime Benli
Background: Calorie restriction (CR) during daily nutrition has been shown to affect the prognosis of many chronic diseases such as metabolic syndrome, diabetes, and aging. As an alternative nutrition model, prolonged intermittent fasting (PF) in humans is defined by the absence of food for more than 12 h. In our previous human studies, CR and PF models were compared and it was concluded that the two models might have differences in signal transduction mechanisms. We have investigated the effects of these models on neurons at the molecular level in this study. Methods: Neurons (SH-SY5Y) were incubated with normal medium (N), calorie-restricted medium (CR), fasting medium (PF), and glucose-free medium (G0) for 16 h. Simultaneously, ketone (beta-hydroxybutyrate; bOHB) was added to other experiment flasks containing the same media. Concentrations of lactate, lactate dehydrogenase (LDH), bOHB, and glucose were measured to demonstrate the changes in the energy metabolism together with the mitochondrial functions of cells. Citrate synthase activity and flow cytometric mitochondrial functions were investigated. Results: At the end of incubations, lactate and LDH levels were decreased and mitochondrial activity was increased in all ketone-added groups (P < .01) regardless of the glucose concentration in the environment. In the fasting model, these differences were more prominent. Conclusion: Our results demonstrated that neurons use ketones regardless of the amount of glucose, and bOHB-treated cells had positive changes in mitochondrial function. We conclude that the presence of bOHB might reverse neuron damage and that exogenous ketone treatment may be beneficial in the treatment of neurological diseases in the future.